Effect of Computer Navigation on Accuracy and Reliability of Limb Alignment Correction following Open-Wedge High Tibial Osteotomy: A Meta-Analysis. - Han, Seung-Beom; Kim, Hyun Jung; Lee, Dae-Hee (BioMed Research International, 2017)
Background. It is unclear whether computer navigation can improve the accuracy and reliability of targeted lower limb alignment correction following open-wedge high tibial osteotomy (HTO). This meta-analysis was designed to compare the accuracy and reliability of limb alignment correction between computer navigated and conventional open-wedge HTOs. Methods. Studies that compared postoperative coronal alignment, including mechanical axis (MA) and weight bearing line (WBL) ratio, outliers of alignment correction, and change in tibial posterior slope, following open-wedge HTO performed using computer navigated and conventional methods were included. Results. Ten studies were included in the meta-analysis. The MA (0.93°; 95% confidence interval [CI]: 0.45–1.41°; P<0.001) and WBL ratio (1.5%; 95% CI: 0.03–2.98%; P=0.048) were significantly greater for computer navigated HTO than for conventional HTO. Outliers of alignment correction after surgery were significantly lower in patients who underwent computer navigated HTO than in those who underwent conventional HTO (odds ratio: 0.25; 95% CI: 0.08–0.79; P=0.02). Changes in posterior tibial slope from before to after surgery, however, were similar for the two approaches. Conclusion. Computer navigated HTO resulted in slightly more valgus postoperative alignment and effectively reduced outliers of alignment correction but had no effect on change in posterior tibial slope when compared with conventional HTO.